PENGARUH ORIENTASI INOVASI DAN TIPE INOVASI TERHADAP KINERJA UMKM INDUSTRI KREATIF DI PROPINSI DIY - Gumirlang Wicaksono; Subarjo Subarjo (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
The objective of this research is to examine the effect of innovation orientation and type of innovation on the performance of Creative Industry UMKM in DIY. This type of innovation includes product innovation and marketing innovation. The research sample is the leader or manager of MSMEs Creative industries in DIY that are engaged in various handicraft industries. Data analysis method uses descriptive statistics that are used to describe innovation orientation, type of innovation, and performance, and inferential statistics are intended for hypothesis testing. The results showed that: there was a positive and significant influence between innovation orientation on product innovation and marketing innovation, there was a positive and significant influence between product innovation and marketing innovation on the performance of MSMEs, there was a positive and significant influence between the orientation of innovation and the performance of SMEs with the type of innovation as mediation.